2014
DOI: 10.1098/rsif.2014.0950
|View full text |Cite
|
Sign up to set email alerts
|

Global rise in human infectious disease outbreaks

Abstract: To characterize the change in frequency of infectious disease outbreaks over time worldwide, we encoded and analysed a novel 33-year dataset of 12 102 outbreaks of 215 human infectious diseases, comprising more than 44 million cases occuring in 219 nations. We merged these records with ecological characteristics of the causal pathogens to examine global temporal trends in the total number of outbreaks, disease richness (number of unique diseases), disease diversity (richness and outbreak evenness) and per cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
406
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(419 citation statements)
references
References 15 publications
3
406
0
10
Order By: Relevance
“…A general increasing trend in disease diversity and outbreak frequency has been observed during recent decades, but the reasons for this are still largely unknown [50]. One contributing factor is the warming climate, which causes changes in disease ecology, outbreak dynamics and seasonality [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…A general increasing trend in disease diversity and outbreak frequency has been observed during recent decades, but the reasons for this are still largely unknown [50]. One contributing factor is the warming climate, which causes changes in disease ecology, outbreak dynamics and seasonality [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence indicating that some pathogens become more prevalent (Chiaramonte, Munson, & Trushenski, 2016; Sterud et al., 2007) and more virulent at warmer temperatures (Smith et al., 2014). For example, it has been shown that increased expression of virulence factors is correlated with increased temperature in Vibrio species (Mahoney, Gerding, Jones, & Whistler, 2010; Oh, Lee, Lee, & Choi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Disease outbreaks -between 1980 and 2013, 12,102 outbreaks of 215 human infectious diseases, including more than 44 million cases, were reported on the Global Infectious Disease and Epidemiology Online Network from 219 nations (Smith et al, 2014). The total number of outbreaks and the diversity of causal diseases (the number of diseases causing outbreaks) have both increased over time (p<0.0001).…”
Section: The Problemmentioning
confidence: 96%